Musculoskeletal Pain during the Menopausal Transition: A Systematic Review and Meta-Analysis - Chang-bo Lu; Peng-fei Liu; Yong-sheng Zhou; Fan-cheng Meng; Tian-yun Qiao; Xiao-jiang Yang; Xu-yang Li; Qian Xue; Hui Xu; Ya Liu; Yong Han; Yang Zhang (Neural Plasticity)
Musculoskeletal pain (MSP) is one of the most severe complaints in women undergoing menopause. The prevalence of MSP varied when taking the menopausal state and age factor into consideration. This study investigated the prevalence of MSP in perimenopausal women and its association with menopausal state. The MEDLINE, Embase, Web of Science, and PubMed databases were searched from inception to July 2020, and 16 studies were retrieved for the current meta-analysis. The primary outcome measure was the MSP Odds Ratio (OR). The estimated overall prevalence of MSP among perimenopausal women was 71% (4144 out of 5836, 95% confidence interval (CI): 64%-78%). Perimenopausal women demonstrated a higher risk for MSP than premenopausal ones (OR: 1.63, 95% CI: 1.35-1.96, P=0.008, I2=59.7%), but similar to that in postmenopausal ones (OR: 1.07, 95% CI: 0.95–1.20, P=0.316, I2=13.4%). The postmenopausal women were at a higher risk of moderate/severe MSP than the premenopausal ones (OR: 1.45, 95% CI: 1.21-1.75, P=0.302, I2=16.5%) or the perimenopausal ones (OR: 1.40, 95% CI: 1.09–1.79, P=0.106, I2=55.4%). In conclusion, the perimenopause is a state during which women are particularly predisposed to develop MSP. As to moderate to severe degrees of MSP, the odds increase linearly with age, from premenopause to peri- and then to postmenopause.